(untitled) (Моделювання, керування та інформаційні технології, 2021)
Worldwide, education innovation is considered a top priority, with the access to and diversity of educational resources having increased significantly since the widespread use of the Internet. Initially, Internet platforms and tools were not directly adapted to the learning process. Along with the mastery of technologies by education specialists, numerous useful resources or tolls have been created, which can be used by all interested teachers and they can become the author of the resource.